2018
DOI: 10.1002/jhet.3393
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Safener Activity, and Molecular Docking of Novel N‐Substituted Thiazide/Thiazole Derivatives

Abstract: A series of novel substituted thiazide/thiazole compounds were designed by splicing active groups and bioisosterism. The title compounds were synthesized via the cyclization, acylation, and carbamylation. All the compounds were characterized by IR, 1H‐NMR, 13C‐NMR, and HRMS. The single crystal of compound 3f was determined by X‐ray crystallography. The biological activity tests indicated that all the compounds showed potential safener activity to the herbicide chlorsulfuron, in which compound 3e showed almost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The MW, log p , HBAs, HBDs, RBs, and other physicochemical properties of compound 21 are close to those of chlorsulfuron, which has high detoxification potency. , The p K a , MW, and electronegativity of compound 8 were also similar to those of the herbicide, indicating great molecular-level similarity of the safener/herbicide . Additionally, both compound 8 and compound 21 were well aligned in a common skeleton with chlorsulfuron through comparison of molecular conformations. , Although the triazine and benzene rings did not exactly coincide, both aromatic rings provided a similar substitution (Figure c). , The same phenomenon was observed between compound 17 , cyprosulfamide (CSA), and diketonitrile (DKN). Compound 17 had better biological activity than CSA, probably because the former had a notably lower p K a than the latter, thereby favoring plant absorption and translocation .…”
Section: Molecular Structure Comparisons Of Safenersmentioning
confidence: 87%
See 2 more Smart Citations
“…The MW, log p , HBAs, HBDs, RBs, and other physicochemical properties of compound 21 are close to those of chlorsulfuron, which has high detoxification potency. , The p K a , MW, and electronegativity of compound 8 were also similar to those of the herbicide, indicating great molecular-level similarity of the safener/herbicide . Additionally, both compound 8 and compound 21 were well aligned in a common skeleton with chlorsulfuron through comparison of molecular conformations. , Although the triazine and benzene rings did not exactly coincide, both aromatic rings provided a similar substitution (Figure c). , The same phenomenon was observed between compound 17 , cyprosulfamide (CSA), and diketonitrile (DKN). Compound 17 had better biological activity than CSA, probably because the former had a notably lower p K a than the latter, thereby favoring plant absorption and translocation .…”
Section: Molecular Structure Comparisons Of Safenersmentioning
confidence: 87%
“…The structure of chlorsulfuron contains phenyl, which rotates right at the active site, resulting in effectively blocking the channel entrance to prevent the substrate from binding to the active site and exerting herbicidal activity. Compound 21 partially blocks the channel entrance, due to the shift to the left of the phenyl portion at the active site (Figure c–e) . In contrast, the entire molecules of IDF and compound 19 rotated to the left at the active center, which only partially blocked the entrance (Figure f–h) …”
Section: Molecular Docking Analysis Of Safenersmentioning
confidence: 98%
See 1 more Smart Citation
“…Ye and Fu’s team designed a series of sulfonylurea-substituted thiazide/thiazole compounds based on bioisosteric replacement, structure–activity relationships (SARs), and active subunit combination. , The sulfonylurea functional group was modified, and the sulfur- and nitrogen-containing heterocycle was retained (Scheme ). The results of the biological activity assay showed that the compound exhibited safener activity against chlorosulfuron.…”
Section: Design Of Novel Herbicide Safeners In Recent Yearsmentioning
confidence: 99%
“…The recently developed condensation method on thiol-containing organoammonium cations is a general and straightforward strategy for the construction of functional A-site cations for new TMHPs. , The reaction is driven by the condensation reaction between thiols on mercaptoethylamine (MEA) or mercaptoethylammonium halide salts (MEAX, X = halogen) and ketones and aldehydes, yielding predesigned dithioketal-containing intercalating cations. It is important to note that the zwitterionic form of MEA is also capable of reacting with ketones under mild conditions to form thiazolidine-derived structures. Inspired by the ring-formation protocol, here, we further investigate the possibility of constructing new SC A-site cations using the thiazolidine-formation reactions between MEA and cyclic ketones (Figure ). Five types of SC cations were successfully made and used to construct corresponding TMHPs with well-defined structures with Ruddlesden–Popper (RP) and Dion–Jacobson (DJ) phases.…”
Section: Introductionmentioning
confidence: 99%